1984
DOI: 10.1055/s-2008-1025871
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction at a Young Age (Under 40 Years)

Abstract: Coronary morphology, risk factors, long-term prognosis, and progression of coronary arteriosclerosis were investigated in 679 (649 mean and 30 women) post-infarction patients under 40 years of age. These patients represented 80% of 844 MI patients under 40 who were referred to our hospital in the years 1973-1980; 20% had refused coronary angiography; 465 patients were followed up for 1-7 years (mean 3.5 years). In 164 patients, a second coronary angiography was performed 3.8 years after the first angiogram, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Roskamm et al (1984) found that of the 679 patients under the age of 40 with acute MI, 8.4% had normal coronary arteries, 57.3% had one-vessel disease, and 34.3% had multivessel disease. There was, however, a significant decrease in the prevalence of zero-vessel disease from those patients below 30 years to the group aged 35-39 years (Roskamm et al, 1984). Uhl and Farre11 (1983) found that 65% of their 81 young MI patients who underwent coronary angiography had multivessel disease, 24% one-vessel disease, and 11% normal coronary angiogram.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Roskamm et al (1984) found that of the 679 patients under the age of 40 with acute MI, 8.4% had normal coronary arteries, 57.3% had one-vessel disease, and 34.3% had multivessel disease. There was, however, a significant decrease in the prevalence of zero-vessel disease from those patients below 30 years to the group aged 35-39 years (Roskamm et al, 1984). Uhl and Farre11 (1983) found that 65% of their 81 young MI patients who underwent coronary angiography had multivessel disease, 24% one-vessel disease, and 11% normal coronary angiogram.…”
Section: Discussionmentioning
confidence: 97%
“…(1980) found that 27% of their patients with zero-vessel disease had exerted themselves to an extreme degree within 24 h preceding the MI, in contrast to 12% of patients with two-or three-vessel disease. Roskamm et al (1984) reported that the acute event was preceded by physical exercise in 60 (1 7%) of 350 patients in whom the relationship to exercise was evaluated. Preceding physical exercise was seen in about 25% of the patients with zero-vessel disease as compared to about 10% of the patients with one-to three-vessel disease (Roskamm et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, these patients are characterized by fewer coronary risk factors than older patients and a higher incidence of normal coronary angiography or single vessel disease [ 5 , 6 ]. The presence of normal coronary angiography is associated with coronary vasospasm, embolism from endocardium or heart vessels, platelet aggregation or spontaneous lysis of thrombus [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only 5% of myocardial infarctions occurring in males under the age of 65 are below 40 years of age. 19 In addition, advanced age has been associated with increased mortality following AMI in many large clinical trials, 20 while young patients entering the hospital have an excellent oneyear prognosis. 21 Similarly, with respect to the in-hospital mortality, the odds of in-hospital mortality increased about 2% with every additional year of the patients' age.…”
Section: Discussionmentioning
confidence: 99%